Nonclinical Profile of BLZ-100, a Tumor-Targeting Fluorescent Imaging Agent. (March 2017) - Parrish-Novak, Julia; Byrnes-Blake, Kelly; Lalayeva, Narine; Burleson, Stefanie; Fidel, Janean; Gilmore, Rhonda; Gayheart-Walsten, Pamela; Bricker, Gregory A.; Crumb, William J.; Tarlo, K. S.; Hansen, Stacey; Wiss, Valorie; et al.
BLZ-100 is a single intravenous use, fluorescent imaging agent that labels tumor tissue to enable more complete and precise surgical resection. It is composed of a chlorotoxin peptide covalently bound to the near-infrared fluorophore indocyanine green. BLZ-100 is in clinical development for intraoperative visualization of human tumors. The nonclinical safety and pharmacokinetic (PK) profile of BLZ-100 was evaluated in mice, rats, canines, and nonhuman primates (NHP). Single bolus intravenous administration of BLZ-100 was well tolerated, and no adverse changes were observed in cardiovascular safety pharmacology, PK, and toxicology studies in rats and NHP. The single-dose no-observed-adverse-effect-levels (NOAELs) were 7 mg (28 mg/kg) in rats and 60 mg (20 mg/kg) in NHP, corresponding to peak concentration values of 89 400 and 436 000 ng/mL and area-under-the-curve exposure values of 130 000 and 1 240 000 h· ng/mL, respectively. Based on a human imaging dose of 3 mg, dose safety margins are >100 for rat and monkey. BLZ-100 produced hypersensitivity reactions in canine imaging studies (lethargy, pruritus, swollen muzzle, etc). The severity of the reactions was not dose related. In a follow-up study in dogs, plasma histamine concentrations were increased 5 to 60 minutes after BLZ-100 injection; this coincided with signs of hypersensitivity, supporting the conclusion that the reactions were histamine based. Hypersensitivity reactions were not observed in other species or in BLZ-100 human clinical studies conducted to date. The combined imaging, safety pharmacology, PK, and toxicology studies contributed to an extensive initial nonclinical profile for BLZ-100, supporting first-in-human clinical trials.